2019
DOI: 10.2298/fil1915931m
|View full text |Cite
|
Sign up to set email alerts
|

A measure of inaccuracy in concomitants of ordered random variables under Farlie-Gumbel-Morgenstern family

Abstract: In communication theory, for possible outcomes of an experiment, we have two basic problems for the statement of the experimenter: we may not have enough information (vague statement) or some of the information may be incorrect, which make inaccurate in either or both of these situations. In this article, a measure of inaccuracy and its residual between distributions of concomitants of generalized order statistics ( os) and parent random variable are extended. Results of inaccuracy for family distributions and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…Moreover, we concluded that the suggested estimators are influenced by sample size and almost give the same behavior in the simulation procedure. In future work, we can extend the obtained models for ordered variables and their concomitants, for more details see [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we concluded that the suggested estimators are influenced by sample size and almost give the same behavior in the simulation procedure. In future work, we can extend the obtained models for ordered variables and their concomitants, for more details see [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we can apply those models to ordered variables and their concomitants for future work. For more details, see [ 17 , 18 , 19 ]. For applications, see [ 20 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they have almost the same value. In future work, we can extend this work to various types of measures such as Tsallis entropy; for more details, see [18] , [19] , [20] , [21] , [22] , [23] , [24] .…”
Section: Discussionmentioning
confidence: 99%